Transcriptomic identification of genes expressed in invasive S. aureus diabetic foot ulcer infection - Agidigbi, Taiwo Samuel; Kwon, Hyuk-Kwon; Knight, James R.; Zhao, Dejian; Lee, Francis Y.; Oh, Irvin (Frontiers in Cellular and Infection Microbiology, 2023)
Infection in diabetic foot ulcers (DFU) are one of the major complications associated with diabetic patients. Staphylococcus aureus is the most common offending pathogen in patients with infected DFU. Previous studies have suggested application of species-specific antibodies against S. aureus for diagnosis and monitoring treatment response. Early and accurate identification of the main pathogen is critical for management of DFU infection. Understanding the host immune response against species-specific infection may facilitate diagnosis and suggest potential intervention options to promote healing infected DFUs. We sought to investigate evolving host transcriptome associated with surgical treatment of S. aureus infected DFU. This study compared the transcriptome profile of twenty-one patients with S. aureus infected DFU who underwent initial foot salvage therapy with irrigation and debridement followed by intravenous antibiotics therapy. Blood samples were collected at the recruitment (0-weeks) and 8-week after therapy to isolate peripheral blood mononuclear cells (PBMC). We analyzed the PBMCs expression of transcriptomes at two different time points (0 vs 8-week). Subjects were further divided into two groups at 8-week: healed (n=17, 80.95%) versus non-healed (n=4,19.05%) based on the wound healing status. DESeq2 differential gene analysis was performed. An increased expression of IGHG1, IGHG2, IGHG3 and IGLV3-21, IGLV6-57 were noted during active infection at 0-week compared to 8-week. Lysine and arginine-rich histones (HIST1H2AJ, HIST1H2AL, HIST1H2BM, HIST1H3B and HIST1H3G) were upregulated at the initial phase of active infection at 0-week. CD177 and RRM2 were also upregulated at the initial phase of active infection (0-week) compared to 8-week follow-up. Genes of heat shock protein members (HSPA1A, HSPE1, and HSP90B1) were high in not-healed compared to healed patients 8-week after therapy. The outcome of our study suggests that identification of genes evolution based on a transcriptomic profiling could be a useful tool for diagnosing infection, assessing severity and assess host-immune response to therapies.